Pengaruh Psikoedukasi Terhadap Tingkat Kecemasan Pada Orang Tua Pasien Di Perina-Nicu RSUD Kabupaten Tangerang - Dewi Sumiyati; Nurry Ayuningtyas Kusumastuti; Ria Setia Sari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Parents with neonatal babies who are being treated in the Perina-NICU have a psychological burden that causes parents to experience anxiety. To reduce the anxiety of parents of patients who are treated in the Perina-NICU, it is necessary to do psychoeducation. The aim of the study was to determine the effect of psychoeducation on the anxiety level of the patient's parents at Perina-NICU RSUD Kabupaten Tangerang. The research method used was a quasi experiment with a one group pretest-posttest design without a control group. The sample in this study were 30 parents whose children were being treated at the Perina NICU. Data were obtained by distributing the Hamilton Anxiety Rating Scale (HARS) questionnaire which was carried out before and after the anxiety management psychoeducation. Univariate and bivariate data analysis using the Wilcoxon test. The results showed that the average anxiety score before psychoeducation was 21.40 and most of the anxiety was in the moderate category, namely 12 (40%). The average anxiety score after psychoeducation was 15.50 and most of the anxiety was in the non-anxious category, namely 12 (40%). There was an effect of psychoeducation on the anxiety level of the parents of babies who are treated in the Perina-NICU with a P value (0.000) < α (0.05). Conclusions and suggestions: there was an influence of psychoeducation on the anxiety level of the parents of babies who are treated at Perina-NICU RSUD Kabupaten Tangerang. It is hoped that psychoeducation will become one of the Standard Operating Procedures (SOP) to reduce the anxiety level of parents of patients treated at the Perina-NICU because the implementation is quite easy and effective.